Training of hip-hop dancers, taking into account the criteria for evaluating performance techniques - Savinykh L.E. ,; Bulgakova O.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study is the scientific and methodological substantiation of the means of technical training for hip-hop dancers. Methods and structure of the study. Pupils of the NaumStyle dance movement school in Surgut, aged 15-17 years, took part in the experiment in the amount of 20 people (10 people each in the experimental group (EG) and control group (CG). Both groups danced five times a week, duration training sessions lasted one hour. Results and conclusions. During the experiment, the content of the criteria for evaluating performance techniques in the direction of “Hip-hop” was revealed: high-quality execution of movements of all styles, precise targeted movements, original drawings and use of the dance floor, naturalness of movements, originality of the manner of performing each style, coherence, teamwork. Based on the identified criteria, such technical training means as: sequential transitions to each individual style technique, special dance sequences from the basic movements of dance styles, musical accompaniment corresponding to the nature and characteristics of each style, patterns of drawings and movements of the team have been developed and introduced into the training process of dancers. dance floor, “Dance Therapy” training, years of “Hip-hop” direction, which during the experiment proved their effectiveness.